Enhancing Elementary Students' Problem-Solving Skills through Modelling Method Integrated with 4C and TPACK Approaches in Islamic Education - Mohamad Shulkhan; Abdelhamid Nechad (FITK UIN Walisongo Semarang, 2026)
This research aims to improve the problem-solving ability of grade II students of SD Negeri Tlogodowo through the application of modelling methods combined with the 4C and TPACK approaches in Islamic Religious Education learning. This study uses the Classroom Action Research (PTK) method through a spiral cycle approach, which includes the planning stages, acting implementation, observing, and reflecting. Data collection techniques are carried out through observation, tests, and documentation. The research was carried out in three cycles which showed a consistent improvement in the learning process and outcomes of students. In Cycle I, the active participation of students is still low so that the results of the formative test have not reached the indicators of completeness. The results of the reflection are then used to improve learning in Cycle II through strengthening small group work, increasing teacher motivation, and improving contextual learning tools in ablution materials. The results showed an increase in the average score to 77 with a completeness of 79%, although some students were still passive. In Cycle III, a more systematic optimization of modelling methods was carried out on tayamum materials accompanied by strengthening learning motivation. The results of the study showed a significant increase, where students became more active, confident, and able to complete tasks well. The observation score reached the very good category with a score of 90, while the learning results obtained an average of 83.33 with 100% completeness. This research contributes to the development of modeling-based Islamic Religious Education learning strategies, 4Cs, and TPACK to improve the problem-solving skills of elementary school students.